2016
DOI: 10.1590/0100-29452016272
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest of Irradiated Tahiti Lime Fruits

Abstract: This study aimed to evaluate the postharvest quality evolution of gamma-irradiated ‘Tahiti’ limes. Shiny, olivegreen fruits with coarse skin (56 cm equatorial diameter) harvested in commercial orchars and processed in commercial packing house line were used. In a preliminary assay, fruits harvested in April 2011 were exposed to a gamma radiation range from 0 to 750 Gy. The 250 and 750 Gy doses negatively affected skin quality and pulp of exposed fruits. For this reason, new assays were carried out using lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…A aplicação de diferentes doses de radiação gama em framboesas (GUIMARÃES et al, 2013), limas ácidas (SILVA et al, 2015) e tomates (SINGH et al, 2016), assim como abacates, tomates e pitaias (DAIUTO et al, 2010;PATARO et al, 2015;MINITKEATKAI;KULTHIP, 2016) tratados com radiação UV-C, não foi observado efeito significativo das doses e fontes irradiantes sobre o pH dos frutos, havendo, contudo, redução nos valores destes com o tempo de armazenamento, similar ao verificado neste trabalho.…”
Section: Resultsunclassified
“…A aplicação de diferentes doses de radiação gama em framboesas (GUIMARÃES et al, 2013), limas ácidas (SILVA et al, 2015) e tomates (SINGH et al, 2016), assim como abacates, tomates e pitaias (DAIUTO et al, 2010;PATARO et al, 2015;MINITKEATKAI;KULTHIP, 2016) tratados com radiação UV-C, não foi observado efeito significativo das doses e fontes irradiantes sobre o pH dos frutos, havendo, contudo, redução nos valores destes com o tempo de armazenamento, similar ao verificado neste trabalho.…”
Section: Resultsunclassified
“…One of the strategies used to obtain seedless fruits is the cultivation of triploid genotypes, such as the acid lime tree 'Tahiti' [Citrus latifolia (Yu. Tanaka)], which has high commercial value and is highly productive (Silva, Bezerra, Bassan, Avilés, & Arthur, 2016). Triploid hybrids in citrus can be obtained from crosses of diploid (2×) parents with tetraploids (4×), hexaploids (6×) with tetraploids (4×) and diploids (2×) with diploids (2×) or open pollinated, in the case of 2× with 2×, the triploid embryos originate from the fertilization of non-reduced female gametes (diploids), with reduced male gametes (haploids), being the natural frequency of obtaining triploides very low (close to 5%), varying according to the maternal genotype (Esen & Soost, 1971, 1973a.…”
Section: Introductionmentioning
confidence: 99%
“…Persian limes are typically harvested and marketed while the peel is still green. Under room temperature, the fruit becomes yellow within a few days, which reduces their commercial viability (Rodrigues da Silva et al 2016). Maintenance of the green color in lime peel postharvest is critical to obtain premium value.…”
mentioning
confidence: 99%
“…As a crucial pest quarantine technique, irradiation treatments have also been reported to maintain fruit color by inhibiting chlorophyll degradation (Srilaong et al 2011); however, other reports have revealed negative effects of irradiation on fruit quality. Rodrigues da Silva et al (2016) found that doses >100 Gy caused accelerated skin yellowing, and doses >150 Gy increased weight loss when subsequently stored at room temperature (24 C) for 20 d. To alleviate this negative impact, a pre-irradiation wax coating application was proposed. Coatings have been used to delay skin discoloration and weight loss in many fruits and vegetables, including lemons (Bai and Plotto 2012).…”
mentioning
confidence: 99%